Il codice Sessoriano 2 - Sara Bischetti (Scrineum Rivista, 2015)
This study aims to be a contribution to the historical reconstruction of the large size biblical witnesses made after the second half of the twelfth-century, i.e. those specimens that in comparison with the Bibbie atlantiche are characterized by a purely imitative connection, as by that time they were devoid of any ideological content. The analysis of the Sessoriano 2 has revealed the deep changes occurred in the oversize holy books dated to the late twelfth-century. Those changes involved methods, techniques of manufacture, as well as the contexts of production. Furthermore, the interdisciplinary approach adopted, in which prevailed the paleographic component, led to a better understanding of the characteristics of the Sessoriano code and to a more precise definition of the geographical and, especially, chronological allocations. So this study proposes a solution to the mixed views among scholars about the interpretation of the subscription written on the last sheet of the manuscript. The accurate paleographic analysis, and the identification of the participation of several hands in the transcription, allowed to establish a positive graphic comparison between the realization of the colophon and the writing of one of the code’s scribes. This hypothesis has contributed to the assignment of the colophon to the same period of the manuscript, allowing the proposal of an ad annum dating and of a precise topographical location.